Structure and mechanics of woven fabrics - Hu, Jinlian (Woodhead publishing in textiles., 2004)
Fabric mechanics are fundamental to the way textiles are designed, tested and manufactured and underpin the way woven fabrics are used. With fully comprehensive coverage of all aspects of fabric anisotropy, stress-strain relationships and fabric drape modelling and testing, Structure and mechanics of woven fabrics, discusses and exemplifies all major aspects of fabric mechanics and their relevance to every stage of the contemporary textile industry. The book is an essential reference for all textile academics, students, researchers, technicians, engineers and technologists, covering all areas.